Collaboration Between Indigenous and Research Communities in the Bering Strait Region - Zdor, Eduard (Études Inuit Studies, 2021)
The Bering Strait region is a unique territory defined by its geographical and sociocultural features. In studying the region, researchers often involve local Indigenous peoples as experts and co-researchers. This paper examines collaboration between research and Indigenous communities, identifies contributors, and describes typical cases of these collaborations. Because this cooperation has a transcultural nature, the article provides an overview of the discussion about the coexistence of two types of knowledge: global scientific knowledge and Arctic peoples’ traditional knowledge. For the same reason, Traditional Ecological Knowledge (TEK) is discussed as both a phenomenon being studied and a research tool. The incorporation and fusion of TEK into scientific methods and management systems has given rise not only to positive results but also to complex and contradictory consequences for both knowledge holders and the knowledge itself.